Sleep Disorders in Children With Celiac Disease: An Analytic Cross-sectional Study - Roohollah Edalatkhah; Zahra Rasoulizadeh; Maryam Mohammadi; Majid Aflatoonian (Caspian Journal of Neurological Sciences, 2025)
Background: Celiac disease (CD) is a complex autoimmune disorder affecting gastrointestinal and extra-gastrointestinal systems. Sleep disorders are prevalent in chronic conditions, but their association with tissue transglutaminase antibody (TTG Ab) levels in pediatric celiac patients is not well-studied. Objectives: This study aimed to determine the association between sleep disorders and TTG Ab levels in pediatric patients with CD. Materials & Methods: This study was conducted on children aged 1 to 16 referred to Shahid Sadoughi Hospital’s Gastroenterology Clinic in Yazd City, Iran, for diagnosis of CD from 2016 to 2022. Sleep quality was assessed using the children’s sleep habit questionnaire (CSHQ), and TTG Ab levels were measured. Results: Out of 55 patients, the mean overall sleep habits score was 60.67±14.85. No significant differences in sleep habits were found based on age, gender, or duration of diet adherence. A statistically significant correlation was found between sleep disorders and elevated TTG Ab levels. Conclusion: Our findings revealed that increased levels of TTG Ab in children with CD are associated with sleep disorders.